DAMPAK ARTIFICIAL INTELLIGENCE TERHADAP POLA KOMUNIKASI MASSA: SYSTEMATIC LITERATURE REVIEW - Gabriella Muskitta; Paramita Hommy; Milka Teterissa (JURNAL BADATI, 2023)
The integration of Artificial Intelligence (AI) in mass communication has fundamentally transformed the media landscape, necessitating a comprehensive understanding of its impacts. This study employs a systematic literature review methodology to analyze 85 peer-reviewed articles published between 2019-2024, examining the multifaceted effects of AI on mass communication patterns. The findings reveal significant transformations in content production efficiency (78%), information distribution patterns (82%), and media consumption behaviors (85%). The study identifies critical challenges in data privacy (92%) and regulatory frameworks (76%). The research also highlights geographical disparities in AI adoption, with predominant studies from North America (32.9%) and Europe (27.1%). This review contributes to the theoretical understanding of AI's role in mass communication and provides practical recommendations for media practitioners, regulators, and researchers. The study concludes that while AI offers substantial benefits in efficiency and personalization, careful consideration must be given to ethical implications, digital divide issues, and regulatory frameworks to ensure responsible implementation.